Decomposition Process and Post Mortem Changes: Review - Teo, Chee Hau; Noor Hazfalinda Hamzah,; Hing, Hiang Lian; Sri Pawita Albakri Amir Hamzah, (Universiti Kebangsaan Malaysia, 2014)
Decomposition is degradation process of a corpse into basic respective constituents macroscopically and microscopically by action of microorganisms, arthropods and scavengers. Post mortem changes could be separated into early post mortem changes (i.e. algor mortis, rigor mortis and livor mortis) and putrefaction stages of corpse. These changes function as suitable indicators for determination of post mortem interval (PMI). In this paper, different stages of post mortem changes, possible variations such as mummification and formation of adipocere and special circumstances such as burial condition is discussed. This article also refers to several arguments in the different texture of adipocere and the influence of different types of fabric in affecting the post mortem changes and formation of adipocere. This is largely due to the property of permeability and resistance of material against degradation process. Undeniably, decomposition process involves numerous potential variables including burial condition, presence of clothing, potential formation of adipocere and mummification. Hence, studies in forensic taphonomy combined with real case scenario are crucial in understanding the nature of decomposition and estimation of PMI with higher accuracy.